2017
DOI: 10.1111/his.13223
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological analysis of primary central nervous system NK/T cell lymphoma: rare and localized aggressive tumour among extranasal NK/T cell tumours

Abstract: Although extremely rare, primary CNS NK/T cell lymphoma does occur and should always be included in the differential diagnosis and we should apply relevant markers routinely in conjunction with exploring the patient background. The accumulation of cases is indispensable to establish an effective treatment strategy for this rare and aggressive malignancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 20 publications
0
26
0
Order By: Relevance
“…[ 1 , 2 ] Extranodal NK/T cell lymphomas are commonly located in the upper respiratory and digestive tracts, such as the nasal cavity, and sometimes occur in the skin or gastrointestinal (GI) tract, but rarely invade the central nervous system (CNS). [ 3 ] Only a few cases of a NK/T cell lymphoma invading the CNS have been reported; [ 4 6 ] here, we reported a case of an extranodal NK/T cell lymphoma in the right middle cranial fossa, with diplopia and facial numbness as the initial presenting symptoms.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…[ 1 , 2 ] Extranodal NK/T cell lymphomas are commonly located in the upper respiratory and digestive tracts, such as the nasal cavity, and sometimes occur in the skin or gastrointestinal (GI) tract, but rarely invade the central nervous system (CNS). [ 3 ] Only a few cases of a NK/T cell lymphoma invading the CNS have been reported; [ 4 6 ] here, we reported a case of an extranodal NK/T cell lymphoma in the right middle cranial fossa, with diplopia and facial numbness as the initial presenting symptoms.…”
Section: Introductionmentioning
confidence: 78%
“…Several articles on extranodal NK/T cell lymphomas involving the CNS or primary CNS NK/T cell lymphomas reported treatment strategies, including MTX-based chemotherapy and radiotherapy. [ 3 , 6 ] However, this treatment strategy is the standard treatment regimen for B cell lymphomas; the curative effect on extranodal NK/T cell lymphoma remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…T-cell lymphomas account for approximately 2-4% of all primary CNS lymphomas in the West [28,29] with a higher incidence in Asia, ranging from 2 to 17% [30][31][32]. Primary CNS T-cell lymphomas (PCNSTL) include peripheral T-cell lymphoma, not otherwise specified, the most common subtype, ALCL, and extranodal NK/T-cell lymphoma [5,26,32,33]. In a series of 45 PCNSTLs from multiple institutions and countries, Shenkier et al reported a wide age range of presentation from 3 to 84 years with median age of 60 years and male predominance, similar to PCNSLs overall [27,34].…”
Section: Discussionmentioning
confidence: 99%
“…The diagnoses were established either on biopsy or by the detection of malignant cells in the cerebrospinal fluid. 12 - 25 …”
Section: Discussionmentioning
confidence: 99%
“…In 1 study evaluating 14 cases (4 newly reported and 10 reported reviewed), none of the patients had B symptoms; however, just like our patient’s clinical course, all patients exhibited aggressive clinical behaviors. 22 …”
Section: Discussionmentioning
confidence: 99%